2001
DOI: 10.1128/iai.69.10.6537-6540.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Nucleotide Sequence, and Expression of the Brucella melitensis sucB Gene Coding for an Immunogenic Dihydrolipoamide Succinyltransferase Homologous Protein

Abstract: The Brucella melitensis sucB gene encoding the dihydrolipoamide succinyltransferase (E2o) enzyme (previously identified as an immunogenic protein in infected sheep) was cloned and sequenced. The amino acid sequence predicted from the cloned gene revealed 88.8 and 51.2% identity to the dihydrolipoamide succinyltransferase SucB protein from Brucella abortus and Escherichia coli, respectively. Sera from naturally infected sheep showed antibody reactivity against the recombinant SucB protein.Brucella spp. are gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
10
0
3
Order By: Relevance
“…In the case of C. burnetii, the antibody responses to SucB protein have been shown to be detected from Q fever patients (16). Furthermore, the SucB proteins of Brucella species, such as B. ovis and B. melitensis have also been found to react with the sera from naturally infected ram and sheep, respectively (24,27). In the present study, the authors showed that the recombinant B. henselae SucB is an immunogenic protein reacting with serum from the immunized mice.…”
Section: Expression and Antigenicity Of The B Henselae Sucbmentioning
confidence: 98%
“…In the case of C. burnetii, the antibody responses to SucB protein have been shown to be detected from Q fever patients (16). Furthermore, the SucB proteins of Brucella species, such as B. ovis and B. melitensis have also been found to react with the sera from naturally infected ram and sheep, respectively (24,27). In the present study, the authors showed that the recombinant B. henselae SucB is an immunogenic protein reacting with serum from the immunized mice.…”
Section: Expression and Antigenicity Of The B Henselae Sucbmentioning
confidence: 98%
“…Several Brucella genes have been cloned, and the proteins that they encode have been characterised [9][10][11][12][13]. However, little is understood regarding the importance of these bacterial proteins in the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not surprising that the MAbs recognize these antigens from both strains. These two proteins were among the earliest antigens to be identified and have been studied as potential vaccine immunogens (19,20,50,51,62). Both proteins were expressed on the surface of S. enterica serovar Typhimurium (20,51), and in both instances, partial protection resulted, much of which was attributed to the cross-reactivity between the surface antigens of S. enterica serovar Typhimurium and those of F. tularensis.…”
Section: Following Recovery From Sublethal Infection Boosting With Hmentioning
confidence: 99%
“…(23,33), Brucella spp. (55,62), and Coxiella burnetii (38), and SucC is considered a diagnostic target as well as a potential vaccine candidate in Leptospira spp. (48).…”
Section: Following Recovery From Sublethal Infection Boosting With Hmentioning
confidence: 99%